An Investigation into the Impact of Elbow Angle, Flow Rate, and Flywheel Diameter on the Performance of a Micro Hydroelectric Power Plant (PLTMH) Prototype - Widiawaty, Candra Damis; Saputra, Yuli Mafendro Dedet Eka; Santoso, Budi; Gunadi, Gun Gun Ramdlan; Sumadipraja, Berlian Firdaus; Yuliana, Arifia Eka; Can, Ahlul Haq; Handaru, Fathir Zuhayr; Khairunisa, Nabila Lufky (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
The Micro Hydroelectric Power Plant Simulator (MHP) serves as a teaching tool to understand the principles and factors influencing electrical power output. While previous studies have examined the impact of turbine types, elbow angles, and flow rates, limited research has focused on the effect of flywheel diameter. The flywheel diameter influences the torque generated for generator rotation. This study, conducted on the MHP simulator at the Energy Laboratory of Jakarta State Polytechnic, explores the effects of variations in elbow angle, flow rate, and flywheel diameter on electrical power output. Experimental results reveal that these parameters significantly impact power generation. Notably, in case 1, with a 45° elbow angle, a flow rate of 7 L/s, and a 30 cm flywheel diameter, the system produces the highest output of 63 W. These findings underscore the importance of flywheel diameter in optimizing micro-hydropower system efficiency, offering insights for future plant design, especially in water-scarce regions. Simulator Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) digunakan sebagai alat pembelajaran untuk memahami prinsip dan faktor yang mempengaruhi keluaran daya listrik. Meskipun penelitian sebelumnya telah mengkaji pengaruh jenis turbin, sudut siku-siku, dan debit aliran, penelitian tentang pengaruh diameter flywheel masih terbatas. Diameter flywheel mempengaruhi torsi yang dihasilkan untuk memutar generator. Penelitian ini dilakukan pada simulator PLTMH di Laboratorium Energi Politeknik Negeri Jakarta untuk menguji pengaruh variasi sudut siku-siku, debit aliran, dan diameter flywheel terhadap keluaran daya listrik. Hasil eksperimen menunjukkan bahwa ketiga parameter tersebut mempengaruhi secara signifikan pembangkit daya listrik. Pada kasus 1, dengan sudut siku-siku 45°, debit aliran 7 L/s, dan diameter flywheel 30 cm, dihasilkan daya tertinggi sebesar 63 W. Temuan ini menekankan pentingnya diameter flywheel dalam mengoptimalkan efisiensi sistem mikro-hidro, yang dapat menjadi acuan perancangan pembangkit mikro-hidro di daerah dengan sumber daya air terbatas.